Estimation Of The Concentration Of Some Heavy Metals In The Euphrates River In Different Areas Of Suq Al-Shuyukh City - Ajel, Marwah Muneam (Academia Open, 2025)
General Background: Environmental pollution, particularly by heavy metals, poses a growing threat to aquatic ecosystems and public health. Specific Background: The Euphrates River, a vital water source in southern Iraq, has been increasingly subjected to pollution from urban and industrial activities. Knowledge Gap: Despite its ecological and economic importance, data on spatial distribution and concentration of heavy metals in Suq Al-Shuyukh remain limited. Aims: This study aimed to estimate the concentrations of lead (Pb), copper (Cu), and cadmium (Cd) in the Euphrates River across different locations in Suq Al-Shuyukh city. Results: Using flame atomic absorption spectroscopy, the study found that concentrations of Pb and Cu were notably higher near riverbanks than midstream, indicating waste accumulation in stagnant waters. Pb levels were consistently the highest, suggesting it as the primary pollutant. Novelty: The study provides new comparative data between river center and bank pollution levels, highlighting critical zones of contamination previously underreported. Implications: The findings emphasize the urgent need for environmental monitoring and remediation strategies to mitigate heavy metal pollution in the Euphrates River, thereby protecting human and ecological health. Highlight : The study confirms elevated concentrations of lead and copper in riverbanks compared to midstream, indicating significant localized pollution. Cadmium, though less concentrated, exceeds WHO safety limits, posing long-term health risks due to accumulation in living organisms. Effective mitigation techniques such as chitosan and biomass treatments are proposed for removing heavy metals from water. Keywords : Heavy Elements, Euphrates River, Environmental Pollution, Suq Al-Shuyukh, Water Contamination